2015
DOI: 10.1589/jpts.27.3619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shoulder stabilization exercise on pain and function in patients with neck pain

Abstract: [Purpose] The objective of this study was to investigate the effects of shoulder stability exercise on pain and function in neck pain patients. [Subjects] The study design consisted of a shoulder stability exercise group and a control group. [Methods] The effects of the therapies were evaluated using a visual analog scale of pain, a pressure pain threshold, neck disability index, cervical range of motion, and a closed kinetic chain test. Each group received treatment five times per week for 4 weeks. [Results] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The participants were given a list and description (with illustrations) for each exercise and were required to demonstrate their ability to perform each exercise correctly. The exercises had been selected on the basis of an overview of source literature [14][15][16][17]. Their goal was to increase the stability and flexibility of the myofascial tissue within the cervical spine.…”
Section: Used Trainingmentioning
confidence: 99%
“…The participants were given a list and description (with illustrations) for each exercise and were required to demonstrate their ability to perform each exercise correctly. The exercises had been selected on the basis of an overview of source literature [14][15][16][17]. Their goal was to increase the stability and flexibility of the myofascial tissue within the cervical spine.…”
Section: Used Trainingmentioning
confidence: 99%
“…Previous research has shown that slow and calm diaphragmatic breathing can activate the vagus nerve, a critical pathway for transmitting and modulating sensory information between the brain and peripheral tissues [ 40 ]. Lee et al (2015) assigned participants with neck pain to two groups, the shoulder stabilization exercise group (SSEG) and the control group [ 41 ]. The study found that the SSEG experienced a significant reduction in PPT in the UT muscles after exercise ( p < 0.05) and had significantly lower NDI scores than the control group ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al () identified a moderate correlation between scapular asymmetry and pain intensity in patients with mild neck pain. A clinical trial conducted by Lee, Shin, and Lee () found that shoulder stabilization exercises reduce pain and increase function in patients with neck pain, supporting the relationship between the cervical region and the scapular and shoulder muscles.…”
Section: Introductionmentioning
confidence: 91%